Driving Factors Behind Changes in Australia’s Immigration Policy (2008–2013): A Case Study of Operation Sovereign Borders - Alif, Nahda Salsabila (Dinasti International Journal of Education Management and Social Science, 2025)
The issue of asylum seekers and refugees has been a persistent challenge for Australia. Despite ratifying the 1951 Refugee Convention and actively participating in multilateral forums such as the Bali Process, Australia, under the Tony Abbott administration in 2013, implemented a controversial unilateral policy known as Operation Sovereign Borders (OSB). This policy emphasised a militaristic approach through "turn-back boats" operations, which appeared to contradict international norms and previous regional cooperation commitments. This thesis aims to analyze the factors driving this shift in Australia's foreign policy. This research employs a qualitative method utilising Charles William Kegley's Foreign Policy Analysis framework, which examines foreign policy decisions through four determinants: Feedback, Global Conditions, Internal Characteristics, and Actor Leadership. The findings indicate that the implementation of OSB resulted from the complex interaction of these four factors. First, the Feedback from the dismantling of the Pacific Solution (2008) triggered a surge in boat arrivals, creating a perception of policy failure. Second, Global Conditions, specifically the global trend of rising refugee numbers combined with Australia's isolated geostrategic position, facilitated maritime interception. Third, Internal Characteristics, including robust military capabilities, the economic burden of onshore processing, and the Coalition Party's electoral victory, provided domestic political legitimacy. Finally, Tony Abbott's Actor Leadership, characterised by conservative values that prioritised border sovereignty over normative international obligations, served as a primary catalyst. The study concludes that OSB is a manifestation of Australia's national security interests (realpolitik), overriding humanitarian approaches and multilateralism.